Glucagon-like peptide 1 and glucose-dependent insulinotropic peptide hormones and novel receptor agonists protect synapses in Alzheimer’s and Parkinson’s diseases - Hölscher, Christian (Frontiers in Synaptic Neuroscience, 2022)
Glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) are peptide hormones and growth factors. A major pathological feature of both Alzheimer’s dis-ease (AD) and Parkinson’s disease (PD) is the loss of synaptic transmission in the cortex in AD and the loss of dopaminergic synapses in the nigra-striatal dopaminergic projection. Several studies demonstrate that GLP-1 and GIP receptor agonists protect synapses and synaptic transmission from the toxic events that underlie AD and PD. In a range of AD animal models, treatment with GLP-1, GIP, or dual-GLP-1/GIP receptor agonists effectively protected cognition, synaptic trans-mission, long-term potentiation (LTP), and prevented the loss of synapses and neurons. In PD models, dopaminergic production resumed and synapses became functional again. Importantly, the GLP-1 receptor agonists exendin-4 and liraglutide have shown good protective effects in clinical trials in AD and PD patients. Studies show that growth factors and peptide drugs that can cross the blood–brain barrier (BBB) better are more potent than those that do not cross the BBB. We therefore developed dual-GLP-1/GIP receptor agonists that can cross the BBB at an enhanced rate and showed superior protective properties on synapses in animal models of AD and PD.